Justify your alpha. (March 2018) - Lakens, Daniel; Adolfi, Federico; Albers, Casper; Anvari, Farid; Apps, Matthew; Argamon, Shlomo; Baguley, Thom; Becker, Raymond; Benning, Stephen; Bradford, Daniel; Buchanan, Erin; Caldwell, Aaron; et al.
In response to recommendations to redefine statistical significance toP ≤ 0.005, we propose that researchers should transparently report and justify all choices they make when designing a study, including the alpha level.